Penerapan Metode ASM yang diperbaiki untuk Optimasi Biaya Distribusi pada Masalah Transportasi Tak Seimbang (Studi Kasus : PT. Pupuk Iskandar Muda) - Tesa Nofri Handayani; Defri Ahmad (Journal of Mathematics UNP, 2023)
Transportation problems is a problem of distributing goods from several sources (supply) to several destinations (demand) with the aim of minimizing distributing costs. The purpose of this study was to determine the optimum cost and optimum allocation in the distribution of subsidized fertilizers at PT. Pupuk Iskandar Muda West Sumatra. This type of research is a type of applied research. The method used in this research is the Revised Version of ASM method which is one of the transportation methods to solve the unbalanced transportation problem with fewer iterations. Base on the result of this study, using the Revised Version of ASM Method, obtained optimum allocation and transportation costs of  IDR 711.072.000. Previously, PT. Pupuk Iskandar Muda spent transportation costs of IDR 913.007.000, so the company experienced a 22.12% reduction in costs.